Jornalismo em quadrinhos: a narrativa na reportagem “Choqueyapu, un río enfermo que nos alimenta” - Cardoso, Larissa da Rosa Rabelo (2022)
This research is about comics journalism, its structure, construction, elements and narrative possibilities. Therefore, the objective of this work is to analyze the narrative of the comic book report “Choqueyapu, Un Río Enfermo Que Alimenta”, also having the intention to debate the constituent elements of the narrative structure of comics, elaborate a methodological procedure to analyze this type of narrative and understand the narrative possibilities in comic book journalism. The comic book article chosen as an empirical object is published on a digital platform and has multimedia elements, is of Bolivian origin and deals with the socio-environmental theme, reporting the contamination of the Choqueyapu River, located in Bolivia. Thus, are presented in the dissertation concepts and reflections about narrative, journalistic narrative, historical trajectory and contextualization of comics, narrative structure of comics, comics journalism and Bolivian socio-environmental context. The methodological approach was based on the relation of Motta's (2013) point of view about narrative in his critical analysis of narrative, with theorists who address the specificities of the structure of comics, such as Eisner (1995), Groensteen (2015) and Postema (2018). Thereby, to analyze the narrative of the comic report, the seven narrative movements proposed by Motta (2013) were considered in the methodological procedures of the dissertation, the specificities of the narrative structure of the comics by authors in the area, and the ordering of discussion of frames indicated by Postema (2018). As a result, it was understood how the object narrative takes place, in addition to understanding the narrative possibilities of comic journalism, promoting the discussion of new formats and narrative approaches in contemporary journalism.